2017
DOI: 10.3389/fimmu.2017.00842
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Sodium Channel-α Mediates the Protective Effect of the TNF-Derived TIP Peptide in Pneumolysin-Induced Endothelial Barrier Dysfunction

Abstract: BackgroundStreptococcus pneumoniae is a major etiologic agent of bacterial pneumonia. Autolysis and antibiotic-mediated lysis of pneumococci induce release of the pore-forming toxin, pneumolysin (PLY), their major virulence factor, which is a prominent cause of acute lung injury. PLY inhibits alveolar liquid clearance and severely compromises alveolar–capillary barrier function, leading to permeability edema associated with pneumonia. As a consequence, alveolar flooding occurs, which can precipitate lethal hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 46 publications
2
53
0
Order By: Relevance
“…The TIP peptide specifically binds to the a subunit of ENaC, but not to the b and g subunits. 20,22 Because depletion of ENaC-a abrogated the protective effects of the TIP peptide in barrier function in toxin-treated human lung microvascular endothelial cell 25 as well as in TNF-induced p38 activation and PGE 2 generation in glomerular endothelial cells (this study), we hypothesize that ENaC-a is the specific receptor for the peptide, although the existence of alternative receptors cannot be fully excluded.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The TIP peptide specifically binds to the a subunit of ENaC, but not to the b and g subunits. 20,22 Because depletion of ENaC-a abrogated the protective effects of the TIP peptide in barrier function in toxin-treated human lung microvascular endothelial cell 25 as well as in TNF-induced p38 activation and PGE 2 generation in glomerular endothelial cells (this study), we hypothesize that ENaC-a is the specific receptor for the peptide, although the existence of alternative receptors cannot be fully excluded.…”
Section: Discussionmentioning
confidence: 80%
“…We demonstrated that the TIP peptide binds to the a subunit of the epithelial sodium channel (ENaC), 20,22 which can be expressed in both epithelial and endothelial cells. 25,26 Support for this experimental direction is provided by the finding that inhaled TIP peptide (a.k.a. AP301 and solnatide) was recently found to be safe in a phase 1 clinical trial in volunteers 27 and displayed promising activities on lung function in 2 phase 2a clinical trials in patients with acute lung injury 28 and after lung transplantation.…”
mentioning
confidence: 99%
“…However, researchers pointed to that TNF‐α‐mediated host responses can resist to pneumococcal infection . In addition, other research showed that PLY can impair endothelial barrier function through decreasing the activity of endothelial sodium channel (ENaC) . Previously demonstrated by other studies, PLY can recognize TLR4, which can also confer the resistance to the bacteria during the infection, and then it can trigger the releasing of TNF‐α .…”
Section: Discussionmentioning
confidence: 99%
“…LLO causes a dysfunction in the ENaC channel in airway epithelial cells, especially by targeting the crucial α subunit [21,315]. ENaC-α is not only crucial for promoting Na + reabsorption across Na + -transporting epithelia but also for its role in strengthening capillary barrier function in lung microvascular endothelial cells [315,316]. Thus, targeting ENaC-α expression impairs structural and functional properties of ENaC and weakens the capillary barrier function [9,316].…”
Section: Listeriolysin O (Llo)mentioning
confidence: 99%
“…ENaC-α is not only crucial for promoting Na + reabsorption across Na + -transporting epithelia but also for its role in strengthening capillary barrier function in lung microvascular endothelial cells [315,316]. Thus, targeting ENaC-α expression impairs structural and functional properties of ENaC and weakens the capillary barrier function [9,316]. LLO decreases the expression of ENaC-α at least partially through disabling positive regulators of ENaC including serum and glucocorticoid-dependent kinase (Sgk-1) and protein kinase B (Akt-1).…”
Section: Listeriolysin O (Llo)mentioning
confidence: 99%